Frequency of Metabolic Syndrome in Patients with Chronic Hepatitis C Virus Infection - Kalim Ullah Khan, Amir Taj Khan, Muhammad Ishfaq, Faramoz Khan, Muhammad Naeem, Muhammad Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The frequent cause of liver disease in the whole world is due to Hepatitis C virus. According to the estimate the worldwide infection due to hepatitis C virus ranges from 150 to 200 million cases. Amongst these cases the chronic infection are found in about 85% cases. In the globe the most important cause of mortality and morbidity is Hepatitis C virus. In the whole world Chronic Liver disease and hepatocellular carcinoma of about 25% is due to hepatitis C virus. Objective: To find out the occurrence of metabolic syndrome in patients with chronic hepatitis C virus infection. Materials and Methods: This study was Descriptive cross sectional research study, which was directed at Department of Medicine, Hayat Abad Medical complex, Peshawar, Khyber Pakhtunkhwa Pakistan. The time duration for our study was 8 month. In our study about 147 patient were observed to find out the frequency of metabolic syndrome in patients with chronic hepatitis C virus infection Results: According to the results of our study, among 147 patients the analysis of age wise distribution was as follow; n= 20-25 Years 6(4.1%), 26-30 Years 26(17.7%), 31-35 Years 51(34.7%), 36-40 Years 28(19.0%), 41-50 Years 22(15.0%) and in 51-60 Years it was 14(9.5%). 49.12 years having standard deviation of ±2.142 was the mean age in our study. In our study gender wise distribution, amongst 147 patients 108(73.5%) were male while 39(26.5%) were female. 131(89.1%) patients were observed to have metabolic syndrome with chronic hepatitis C virus infection. Conclusion: Our study concludes that there is no uncommon occurrence of metabolic syndrome in cases with HCV infection. There is significant association of metabolic syndrome with Hepatitis C Virus (HCV) when HCV infection have more than 3 year’s duration. Keywords: Frequency; Metabolic Syndrome; Chronic hepatitis C virus infection; Mortality; Morbidity